The link between ultra-processed food consumption, fecal microbiota, and metabolomic profiles in older mediterranean adults at high cardiovascular risk - Alessandro Atzeni; Adrián Hernández-Cacho; Nadine Khoury; Nancy Babio; Clara Belzer; Jesús Vioque; Dolores Corella; Montserrat Fitó; Clary Clish; Josep Vidal; Prokopis Konstanti; Sandra Gonzales-Palacios; et al. (Nutrition Journal)
Abstract Background Ultra-processed food (UPF) consumption has been linked to adverse metabolic outcomes, potentially mediated by alterations in gut microbiota and metabolite production. Objective This study aims to explore the cross-sectional and longitudinal associations between NOVA-classified UPF consumption, fecal microbiota, and fecal metabolome in a population of Mediterranean older adults at high cardiovascular risk. Methods A total of 385 individuals, aged between 55 and 75 years, were included in the study. Dietary and lifestyle information, anthropometric measurements, and stool samples were collected at baseline and after 1-year follow-up. Fecal microbiota and metabolome were assessed using 16 S rRNA sequencing and liquid chromatography-tandem mass spectrometry, respectively. Results At baseline, higher UPF consumption was associated with lower abundance of Ruminococcaceae incertae sedis (β = − 0.275, P = 0.047) and lower concentrations of the metabolites propionylcarnitine (β = − 0.0003, P = 0.013) and pipecolic acid (β = − 0.0003, P = 0.040) in feces. Longitudinally, increased UPF consumption was linked to reduced abundance of Parabacteroides spp. after a 1-year follow-up (β = − 0.278, P = 0.002). Conclusions High UPF consumption was associated with less favorable gut microbiota and metabolite profiles, suggesting a possible link to reduced short-chain fatty acid (SCFA) production, altered mitochondrial energy metabolism, and impaired amino acid metabolism. These findings support the reduction of UPF consumption and the promotion of dietary patterns rich in fiber for better gut health. Further research is needed to confirm these associations and clarify the underlying mechanisms. Trial registration : ISRCTN89898870 ( https://doi.org/10.1186/ISRCTN89898870 ).